ANCIENT VOLCANOGENIC MASSIVE SULFIDE DEPOSITS IN CHINA - Massive Sulfide Deposits in the Changning-Menglian Back-arc Belt in Western Yunnan, China: Comparison with Modern Analogues in the Pacific - Kaihui Yang; Steven D. Scott; Xuanxue Mo (Canadian Institute of Mining, Metallurgy and Petroleum, 1999)
Abstract -The Changning-Menglian metallogenic belt in western Yunnan, China, is characterized by the occurrences of both Pb-Zn-Cu and Cu massive sulfides in Permo-Carboniferous mafic volcanic sequences. These deposits were formed in a back-arc basin at a rifted continental margin in the Paleozoic Tethys Ocean. Pb-Zn-Cu deposits are associated with alkalic basalt, andesite, and lesser felsic volcanic rocks intercalated with limestone, which probably formed along an immature rifting segment on a continental basement. These volcanic rocks are enriched in K, Ti, LREE, and other incompatible elements, and have the attributes of alkalic within-plate basalt. An extensive unit of sulfide- carbonate-silica shale in proximity to massive sulfides contains high values of Mn, As, Mo, W, Sn, Sb, and Hg, and has REE patterns that are similar to the volcanic rocks. This, together with the graded bedding in the footwall volcanic rocks, suggests that the sulfides precipitated in a shallow, unstable, and carbonate-saturated volcanic basin. A stringer zone is traced downward for 500 m below the massive sulfide orebodies. It is characterized by an upper sericite-quartz zone and an extensive lower skarn alteration with enhanced W, Sn, and Bi. Lead isotope data show both continental basement and magmatic sources may have supplied the ore metals. Cu deposit and occurrences are hosted by tholeiitic units that represent the mature spreading segments in the back-arc basin. The tholeiitic lavas have LREE-depleted or flat REE patterns similar to MORB or back-arc mafic lavas. The cupriferous massive sulfides are overlain by an extensive unit of chlorite-magnetite or ochre, suggesting a relatively oxygenated oceanic basin. Ni and less Co mineralization is found in dolomite veins of the stringer zone. Enhanced concentrations of Ni, Co, Au, and As are found in the massive sulfides and in sulfide-rich tuffites. The geological setting and mineralization of the Changning-Menglian belt has similarities with modern back-arc basins such as the Manus Basin in the western Pacific.